2014
DOI: 10.1016/j.yjmcc.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban interactome in cardiac contractility and survival: A new vision of an old friend

Abstract: Depressed sarcoplasmic reticulum (SR) calcium cycling, reflecting impaired SR Ca-transport and Ca-release, is a key and universal characteristic of human and experimental heart failure. These SR processes are regulated by multimeric protein complexes, including protein kinases and phosphatases as well as their anchoring and regulatory subunits that fine-tune Ca-handling in specific SR sub-compartments. SR Ca-transport is mediated by the SR Ca-ATPase (SERCA2a) and its regulatory phosphoprotein, phospholamban (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
115
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 74 publications
10
115
0
Order By: Relevance
“…PLN is one of the primary regulators of SERCA2a (27). When PLN binds to SERCA2a, it inhibits the Ca 2+ pumping function and thus reduces the ability of the SR to acquire and store Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLN is one of the primary regulators of SERCA2a (27). When PLN binds to SERCA2a, it inhibits the Ca 2+ pumping function and thus reduces the ability of the SR to acquire and store Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…In the work presented here, we show that STIM1 is present but that its function in heart is distinct from the canonical SOCE behavior and does not contribute to Ca 2+ influx through I SOCE . Instead we show that STIM1 binds phospholamban (PLN), an endogenous SERCA2a inhibitor in the heart (27), and by doing so reduces the PLN-dependent inhibition of SERCA2a and thereby indirectly activates SERCA2a.…”
mentioning
confidence: 84%
“…It has been shown that decreased phosphorylation of PLN, and an increase of the PLN to Ca 2+ ATPase pump ratio leads to contractile dysfunction. 15 In vitro studies have revealed that higher phosphorylation levels of PLN lead to improved contractility, and that its dephosphorylation may promote heart failure. 27 for dysfunctional intercalated discs.…”
Section: Desmosomal Moleculesmentioning
confidence: 99%
“…14 Especially PLN phosphorylation has been reported to play a key role in the pathophysiology of heart failure. 15 Taken together, various cellular pathways, particularly electromechanical cell-to-cell coupling, inflammation, apoptosis, adipogenesis and fibrosis seem to be involved in the pathophysiology of ARVC/D, but the interactions are not fully understood. Therefore, the aim of this study was to identify dysregulated myocardial molecules associated with the mentioned pathways ARVC/D by investigating the myocardial expression profiles of various candidate proteins using an mRNA expression and immunolocalization approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation